Operation Optimization Method of Energy Storage System with Two-Part Tariff - Yiwei CHEN; Xiao QIAN; Yi TANG; Lei ZHONG; Lu YIN; Yanan FU (Zhongguo dianli)
With the rising opportunities from the two-part tariff and the development of energy storage, massive economic benefits will become available for customers by installing energy storage system. In order to explore the economic potential of energy storage system, based on the calculation of the lower bound of the maximum load at demand end, this paper proposes an optimal operation model of energy storage system to achieve the maximum benefits. In this model the maximum load demand and energy storage power are chosen as the control variables, and the energy storage system operation and lifespan, variable association, etc. are taken into full consideration as the constraints. With the aids of the proposed auxiliary variables, the nonlinear optimization operation model is transformed into a linear model, which greatly reduces the complexity of solution. Finally, the model has been implemented successfully in Beijing and Shanghai regions to analyze the benefits of energy storage system in the typical scenarios.